The piratization of Russia : Russian reform goes awry - Goldman, Marshall I. (Routledge, 2003)
Examines the debacle of Russian reform, especially the emergence of oligarchs accused of using guile, intimidation and violence to reap riches. Explains Russia's problems and how they could have been avoided.